Imines as threefold functional devices: motional, photochemical, constitutional - Greb, Lutz; Vantomme, Ghislaine; Lehn, Jean-Marie (Molecular photoswitches, 2022)
Imine-type molecules represent threefold functional devices: photochemical, motional, and constitutional. Their photochemically and thermally driven configurational and conformational switching processes make chiral imines the simplest prototype of light-driven rotary molecular motors. They induce shape switching with modulation of complexation properties as well as constitutional adaptation under component exchange. The triple dynamics of imines, configurational, conformational, and constitutional, are versatile tools to reach functions of higher complexity in molecular systems. They form an attractive class of compounds by their synthetic accessibility, their stability, and their modularity. This chapter highlights seminal examples of implementation of imine-type switches in molecules and materials.
Gesehen am 04.10.2022